Parâmetros histológicos e produção de ovos de codornas em postura alimentadas com milho tratado com óleos essenciais - Rodrigues, Julianne Almeida (2017)
The aim of this study was to verify the effect of essential oils extract of plants used as natural alternative in the control of stored grain pests on the posture phase and histological parameters of specific organs such as kidney, liver, lung and spleen, besides the weight control of Japanese quails. The experiment was carried out in the experimental area of the Universidade Federal do Espírito Santo. Was used five essential oils (Black Pepper, Pine, Ginger, Lemongrass and Rosemary) plus control (only ration), diluted in 1% solution and incorporated into the ration in the proportion of 3% in relation to the total food, being 6 treatments (6 replicates), constituting 36 experimental units, each with 8 Japanese quails evenly distributed according to weight and posture. The basal diet (control) was formulated based on soybean meal and corn. The experiment was conduct during 42 days. Thirty-six animals were euthanized, one animal per experimental unit. The variables analyzed were: posture rate, and histological parameters of the liver, kidney, lung and spleen. The animals presented alterations in their histological parameters, mainly in the liver, it was observed in all groups (essential oils and control group) a greater number of degeneration near the centrilobular vein. The group of animals fed with essential oil of Rosemary presented the highest occurrence of fibrosis in the portal space. In the kidney, the presence of discrete degeneration was observed in all treatments, including in the control group. Only one of the animals belonging to the treatment with pine showed marked tubular degeneration. In the spleen it was verified the presence of proliferation of white safflower cells in all animals, and those that received pine essential oil were the ones that presented the greatest number of animals with marked intensity. In the lungs, the animals belonging to the group that received essential oil of black pepper were the ones that presented the highest number of animals with multifocal and focal inflammatory infiltrates. The lowest posture rate was presented for the treatments with the essential oils of ginger, lemon grass and rosemary, however, they were similar to the control, and no difference was observed in the feed consumption of the animals.